2017
DOI: 10.1177/0146167217697695
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Interpersonal Features of Intellectual Humility

Abstract: Four studies examined intellectual humility-the degree to which people recognize that their beliefs might be wrong. Using a new Intellectual Humility (IH) Scale, Study 1 showed that intellectual humility was associated with variables related to openness, curiosity, tolerance of ambiguity, and low dogmatism. Study 2 revealed that participants high in intellectual humility were less certain that their beliefs about religion were correct and judged people less on the basis of their religious opinions. In Study 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
314
1
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(341 citation statements)
references
References 61 publications
(85 reference statements)
10
314
1
16
Order By: Relevance
“…This research made use of numerous independent samples and used multiple measures to assess the predictors and outcomes. The findings replicate and expand previous studies using different measures of IH, thereby strengthening confidence in previous results and increasing understanding about the many ways IH is connected to knowledge acquisition (Alfano et al, 2017;Davis et al, 2016;Deffler et al, 2016;Leary et al, 2017). Additional work can be done to relate IH to immediate measures of knowledge acquisition.…”
Section: Conclusion Limitations and Future Directionssupporting
confidence: 83%
See 1 more Smart Citation
“…This research made use of numerous independent samples and used multiple measures to assess the predictors and outcomes. The findings replicate and expand previous studies using different measures of IH, thereby strengthening confidence in previous results and increasing understanding about the many ways IH is connected to knowledge acquisition (Alfano et al, 2017;Davis et al, 2016;Deffler et al, 2016;Leary et al, 2017). Additional work can be done to relate IH to immediate measures of knowledge acquisition.…”
Section: Conclusion Limitations and Future Directionssupporting
confidence: 83%
“…Previous research has suggested links between IH and need for cognition (NFC; Davis et al, 2016) and curiosity (Leary et al, 2017). Further, NFC is associated with less belief in the certainty of knowledge (Kardash & Scholes, 1996), which may also promote IH.…”
Section: Thinking Styles Interpersonal Dispositions and Learning Gomentioning
confidence: 96%
“…Intellectual humility is defined by a person's independence of intellect and ego, openness to revising one's viewpoint, respect for others' viewpoints, and a lack of intellectual overconfidence, and is therefore argued to promote human thriving through tolerance of other's ideas, collaboration, and civil discourse (Krumrei-Mancuso & Rouse, 2016). Indeed, people with higher levels of intellectual humility are less inclined be judgmental of people with whom they disagree (Leary et al 2017). Hence, if people high in cognitive ability show more genuine openness and respect for other viewpoints compared to people lower in cognitive ability, they should display an overall stronger support for any group to exercise its freedom of speech.…”
mentioning
confidence: 99%
“…As compared to intelligence, wisdom also appears to be uniquely associated with prosocial and eudaimonic tendencies (e.g., cooperative intentions and behavior, growth orientation; [49,[101][102][103]), a willingness to forgive friends and family members one has a dispute with [57], as well as more prosocial behavior in economic transactions [104]. Moreover, and particularly pertinent to intergroup issues, wisdom is associated with reduced political bias [105], reduced intergroup attitude polarization across several heightened intergroup conflicts [106] (unpublished manuscript), and the willingness to consider diverse viewpoints during political elections in the US [107], with such aspects of wise reasoning as an appreciation of diverse viewpoints facilitating accuracy in the forecasting of geopolitical events [108].…”
Section: Civic Discoursementioning
confidence: 99%